Gender differences in the determinants of mature entrepreneurship? The case of Germany - Romeu Gordo, Laura; Stypińska, Justyna; Franke, Annette (Frontiers in Sociology, 2022)
Female entrepreneurs aged 45 and older represent a non-traditional model of self-employed workers in both ways: in terms of gender and age. The transition into self-employment for women aged 45 years and older represents a topic of aging research that still tends to be overlooked. Previous studies found ambivalent results for the issue regarding motives and entrepreneurial pathways between former employment – or unemployment – and starting one’s own business and the ways in which these entrepreneurial activities are shaped by social differences (such as gender) and biographically accumulated resources and restrictions. This article studies biographical-related factors and motivations that determine what is variously referred to as “senior”, “mature” or “late-career” entrepreneurship for men and women aged 45 and above. Using data from the German Socio-Economic Panel (SOEP), the descriptive analysis explains the main gender differences among people within the target age group who have taken the step into self-employment. The multivariate analysis interrogates the main determinants that govern any increase in the probability of becoming self-employed after the age of 45 and seeks to identify the main differences between women and men in relation to such determinants. The results show substantial gender-based occupational segregation in entrepreneurship patterns in different age groups, with men working longer hours on average than women and enjoying higher average earnings. However, the multivariate analysis shows that the main drivers for mature entrepreneurship are similar for both men and women and that necessity represents an important factor for everyone for starting a business.